Elevated concentrations of metal(loids) in seaweed and the concomitant exposure to humans - Khandaker, Mayeen Uddin *; Chijioke, N. O.; Nurul Adillah, H.; Bradley, D.A. *; Alsubaie, A.; Sulieman, Abdelmoneim; Faruque, M. R. I.; Sayyed, M. I.; Al-mugren, K. S. (MDPI, 2021)
While the consumption of seaweed and seaweed-based products is very common amongst East Asian nations, forming a notable component of the daily diet, relatively very few studies have concerned the concentrations of heavy metals in these together with potential effects on human health. The present study analyses the concentrations of 17 elements in locally resourced seaweed, also assessing potential noncarcinogenic and carcinogenic risks. The samples were ground, homogenized, and quantified using the ICP-OES technique. It has been found that the essential elements K, Ca, Mg, Zn, and Na typically show concentrations somewhat greater than a number of potentially toxic metals, in particular, Cd, Pb, Ag, and As, with exceptions being Ni, Cr-VI, and Si. Statistical analysis indicates all of the latter to have similar origin, with increased concentration of these metals within the marine ecosystem. While the daily estimated intake of most metals is seen to be within the daily dietary allowance level recommended by various international organizations, the noncarcinogenic risk shows a value greater than unity, estimated via the hazard quotient. This indicates a potential for adverse effects to health arising from consumption of the sampled seaweed. The carcinogenic risk resulting from nonessential elements shows values greater than the United States Environmental Protection Agency (US-EPA) reference limit of 10−4 . Considering the nonbiodegradability of heavy metals and metalloids and their potential accumulation in seaweed, there is need for critical examination of metal levels in the seaweeds obtained from the present study locations, together with the introduction of practices of removal of heavy metals via bio-adsorbent techniques.